2017
DOI: 10.3847/1538-4357/835/2/201
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Pressure in the Cold Neutral Medium of Nearby Galaxies

Abstract: Dynamic and thermal processes regulate the structure of the multi-phase interstellar medium (ISM), and ultimately establish how galaxies evolve through star formation. Thus, to constrain ISM models and better understand the interplay of these processes, it is of great interest to measure the thermal pressure (P th ) of the diffuse, neutral gas. By combining [C II] 158 µm, HI, and CO data from 31 galaxies selected from the Herschel KINGFISH sample, we have measured thermal pressures in 534 predominantly atomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 67 publications
9
60
1
Order By: Relevance
“…This is to say that our data suggests that local Universe spirals are consistent with theoretical predictions of Σ SFR − P from feedback regulated star formation models. This is similar to the results of Herrera-Camus et al (2017) who find that KINGFISH galaxies, with P/k ∼ 10 3 .5 − 10 4 .5 are consistent with predictions from Kim et al (2013).…”
Section: Balance Of Star Formation and Pressure In Gas Rich Diskssupporting
confidence: 91%
“…This is to say that our data suggests that local Universe spirals are consistent with theoretical predictions of Σ SFR − P from feedback regulated star formation models. This is similar to the results of Herrera-Camus et al (2017) who find that KINGFISH galaxies, with P/k ∼ 10 3 .5 − 10 4 .5 are consistent with predictions from Kim et al (2013).…”
Section: Balance Of Star Formation and Pressure In Gas Rich Diskssupporting
confidence: 91%
“…Given that the σ and Σ values we measure resemble those typically found for HI, the internal pressure in the molecular gas is likely comparable to the ambient medium pressure in these galaxies. Reinforcing this view, the pressures implied by our measurements approach the thermal pressures found by Herrera-Camus et al (2017) in the HI dominated parts of KINGFISH galaxies. They showed that these thermal pressures are typically a factor of ∼ 3 lower than the ambient gas pressure.…”
Section: Interpretations Of σ Excess At Low σsupporting
confidence: 87%
“…C). The resulting pressure is then about 10 2.5−5 K cm −3 , which is similar to what is found in predominantly atomic gas within Herschel KINGFISH galaxies (Herrera-Camus et al 2017) T H2 : fixed 4) n H2 : pressure eq. / overdense → N(H 2 |C + ) I([CII]) (mol.)…”
Section: Modeling Strategysupporting
confidence: 76%
“…In the neutral gas, C + may exist in the H 0 phase but also in the H 2 phase, in regions where CO is photodissociated while H 2 is self-shielded and shielded by dust, the so-called CO-dark molecular gas (e.g., Madden et al 1997;Grenier et al 2005;Wolfire et al 2010). The [C ii] line has been used to trace the star-formation rate (SFR; e.g., De Looze et al 2014;Pineda et al 2014), to infer physical conditions in photodissociation regions (PDRs), and to calculate the CO-to-H 2 conversion factor (X CO ; e.g., Jameson et al 2018;Herrera-Camus et al 2017;Pineda et al 2017). The growing number of observations in both Galactic and extragalac-tic environments (with routine detections at z > 6; e.g., Aravena et al 2016) has renewed the interest in understanding [C ii] as a diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%